Growing of Sheashum on the Sand Dunes of Araria Plains as Studied at Soil Conservation Research Station Jalalgarh - Mahanta, G.C. (Journal of Soil and Water Conservation, 2022)
The Research Station is situated in the civil district of Purnea (Bihar) and represents the Araria plains which extends roughly in 150 square miles from North to South. The land comprises mostly of sand dunes, sandy and loamy soil having 6" to 18" depth. The infiltration and permeability capacity of the soil is very high. The annual rainfall is nearly 60" and mostly spreads over a period of five months i.e. May to September.